Studi Hubungan Antara Faktor Lingkungan Fisik Rumah Dengan Penderita TB Paru BTA di Aceh Selatan - Mawardi Mawardi; Rychad Sambera; Irma Hamisah (Jurnal Serambi Engineering, 2019)
Pulmonary TB is a world problem especially in developing countries including Indonesia. In Indonesia, it is estimated that every year 450,000 new cases of pulmonary TB appear with death estimated at 175,000 per year.  his study aims to determine the relationship between physical environmental factors of houses with pulmonary TB patients with AFB (+) at Lhok Bengkuang Health Center, Tapaktuan Subdistrict, South Aceh Regency in 2018. The population in this study were pulmonary TB patients smear (+) recorded in the case data report in the working area of Lhok Bengkuang Health Center, Tapaktuan Subdistrict, South Aceh Regency  in 2017, which is 36 patients with pulmonary TB (+) and 36 non-pulmonary TB sufferers. The results of the  nivariate study showed 52.8% of respondents with occupant density did not meet the requirements, 55.6% of respondents with house floors did not meet the requirements, 51.4% of respondents with lighting did not meet the requirements, 51.4% of respondents with house ventilation did not meet the requirements . The results of bivariate analysis showed that there was a relationship between occupant density (P value = 0.001), house floor (P value = 0.015), lighting (P value = 0.034), ventilation (P value = 0.038) with pulmonary TB patients with AFB (+) in the area of Lhok Bengkuang District Health Center, Tapaktuan Subdistrict, South Aceh Regency.